P0739PANEL OF SENSITIVE BIOMARKERS OF THE PRIMARY RESPONSE TO RENAL INJURY FOR AN EARLY DIAGNOSIS OF CHRONIC KIDNEY DISEASE. (6th June 2020) - Valente, Maria João; Rocha, Susana; Lousa, Irina; Reis, Flávio; Nunes, Sara; D. Viana, Sofia; Preguiça, Inês; Mira, Filipe; Nogueira, Rui; Coimbra, Susana; Catarino, Cristina; Rocha-Pereira, Petronila; et al.
Abstract: Background and Aims: The identification of early kidney injury biomarkers is of utmost importance, since most widely used markers of kidney function vary only after several biological changes. Biomarkers allowing an earlier diagnosis of chronic kidney disease (CKD) would avoid delays in the treatment of patients. It is unlikely that a single marker is sufficient to detect the onset of CKD considering the multiple pathophysiological changes underlying primary renal response to renal injury. Several markers of inflammation, endothelial (dys)function, glomerular and tubulointerstitial injuries have been proposed and could be used combined as a panel of markers with different specificities, allowing an early detection of renal injury. Our aim was to study a panel of biomarkers proposed as early markers of renal injury, with different specificities, to evaluate and compare their sensitivities at different CKD stages. Method: In this preliminary study, we enrolled 22 healthy individuals and 27 CKD patients separated into 3 groups, according to the CKD stage: 9 in stages 1 and 2; 9 in stage 3, and 9 in stages 4 and 5. None of the patients presented inflammatory, infectious or neoplastic diseases. Diagnosis and CKD stage assignment were performed according to KDIGO guidelines. We evaluated circulating levels of cystatin C (CystC), creatinine (Cr), beta trace protein (BTP) as markers of renal function; tissue inhibitor metalloproteinase 1 (TIMP-1), neutrophil gelatinase-associated lipocalin (NGAL) and transforming growth factor-β (TGF-β) as markers of interstitial tubulointerstitial injury; asymmetric dimethylarginine (ADMA) and tissue plasminogen activator (t-PA), as markers of endothelial (dys)function; pentraxin 3 (PTX3), interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α), as markers of inflammation; and, pro B-type natriuretic peptides (proBNP), as a marker of cardiac (dys)function. Results: In early stages of CKD (1 and 2), we found significant changes in markers of renal function (BTP, but not Cr and CystC), of tubular interstitial injury (TIMP-1 and TGF-β), of inflammation (TNF-α), of endothelial (ADMA) and cardiac (proBNP) dysfunction ( vs. controls). In stage 3, we found significant changes ( vs. stages 1-2) in markers of renal function (Cr and CystC), inflammation (TNF-α, IL-6), endothelial dysfunction (t-PA) and tubulointerstitial injury (TIMP-1); in stages 4-5 ( vs. stage 3), we found significant changes only in the classic marker, Cr, and a trend towards increased CystC. Moreover, we found that at stages 1-2 all patients showed higher levels of BTP and proBNP when compared to the median value in the control group; TIMP-1 and ADMA were increased in 7/9 patients; TNF-α was increased in 7/9 patients; and 7/9 patients had lower values of TGF-β compared to the median value of controls. For the classical markers, Cr and CystC, we found that 5/9 and 4/9 patients, respectively, had lower values than the median value of controls; however, only 2/9 patients showed abnormal creatinine values ( vs. reference values). Conclusion: Our data suggest that a panel including classic (Cr and CystC) and more sensitive blood markers of the primary response to renal injury (BTP, TIMP-1 or TGF-β, ADMA, TNF-α and proBNP) would allow an earlier diagnosis of CKD, avoiding a delay in diagnosis and management of CKD patients.